Factors conditioning the implementation of the smart city concept - Chomiak-Orsa, Iwona; Sosgórnik, Agnieszka (Determinanty warunkujące implementację koncepcji smart city, 2020)
Due to the scale of urban development as well as the level of urbanization of society, increasing problems are being identified in achieving the effective management of urban space. Problems of the communication system, media management and the efficient implementation of administrative processes are the main reasons for the search for technological solutions that would automate the operational processes of city management. The aim of the article was to identify and indicate the main areas of the functioning of cities that undergo technological transformation in order to improve the service of processes. The research methods used in the article were the analyses of literature and of the smart urban solutions used in Polish cities. The development and functioning of cities have a huge impact on the natural environment and general living conditions of the inhabitants. Due to the problems arising from urbanization, innovations are tested in cities to solve them. An example of this is the concept of smart city and the related technologies. Firstly, it is worth looking at the process of urbanization and the conditions for the development of urban areas. cities such as Wrocław, Poznań, Gdańsk and Łódź
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 2 (56), s. 20-29
Keywords: smart city; e-administration; urbanization; smart networks; Internet of things; inteligentne miasto; e-administracja; urbanizacja; inteligentne sieci; internet rzeczy